Improving food resilience through community awareness on cooking oil distribution - Wibisono, Yudhiawan; Maarif, Mohammad Syamsul; Yulianto, Budi; Asikin, Zenal (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to strengthen food security through public awareness in the cooking oil trade system. Food security remains a pressing challenge in many developing countries, where staple commodities like cooking oil are vital to daily nutrition and economic stability. While much attention has been given to improving production and distribution systems, the role of public awareness in strengthening food security is often underestimated. This study uses a descriptive qualitative approach with a literature review method. This paper explores how consumer education and community-based awareness initiatives can enhance the efficiency, transparency, and sustainability of the cooking oil trade system. By empowering individuals with knowledge about market dynamics, responsible consumption, and supply chain challenges, public awareness serves as a strategic tool to reduce panic buying, prevent waste, and promote equitable access. The study highlights the potential for collaborative efforts between government, industry stakeholders, and civil society to integrate educational campaigns into food trade policies. This study gives novelty in raising public awareness is shown to be a critical and cost-effective measure in building more resilient and food-secure communities.